2004
DOI: 10.1590/s0103-50532004000500025
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid constituents from leaves of Guarea kunthiana

Abstract: sesquiterpenos (alismol, alismóxido, espatulenol e 4β,10α-aromadendranodiol), poliprenol-12 e α-e δ-tocoferóis. Kolavenal está sendo relatado pela primeira vez como produto natural, assim como a ocorrência de diterpenos do tipo cembrano e ent-caurano na família Meliaceae.From leaves of Guarea kunthiana one new kaurene diterpene (ent-kaur-16-en-2-one) was isolated along with eight known diterpenes (ent-kaur-16-ene, ent-3α-and 3β-hydroxykaur-16-ene, kolavelool, kolavenol, kolavenal, ent-13-epi-manoyloxide and (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Studies conducted on extracts from the roots of this plant have reported antiparasitic (Lima, 2006;Mesquita et al, 2005) and insecticidal (Coelho, 2006) activities. Phytochemical studies have indicated the occurrence of diterpenes and sesquiterpenes in ethanolic extract obtained from the leaves of G. kunthiana (Garcez et al, 2004) and a limonoid ecuadorin isolated from the dichloromethane extract of the leaves (Mootoo et al, 1992). However, the antimicrobial and antioxidant potential and the chemical composition of the essential oil of G. kunthiana have not been reported in the literature.…”
Section: Agentsmentioning
confidence: 99%
“…Studies conducted on extracts from the roots of this plant have reported antiparasitic (Lima, 2006;Mesquita et al, 2005) and insecticidal (Coelho, 2006) activities. Phytochemical studies have indicated the occurrence of diterpenes and sesquiterpenes in ethanolic extract obtained from the leaves of G. kunthiana (Garcez et al, 2004) and a limonoid ecuadorin isolated from the dichloromethane extract of the leaves (Mootoo et al, 1992). However, the antimicrobial and antioxidant potential and the chemical composition of the essential oil of G. kunthiana have not been reported in the literature.…”
Section: Agentsmentioning
confidence: 99%
“…Thus, clerodanes and cembranoids are biosynthetically related, and were reported to coexist in the same plant material, such as Echinodorus macrophyllus [14,15], and Guarea kunthiana [16]. However, to the best of our knowledge, Croton oblongifolius [17,18] was the only species from genus Croton that was reported to produce clerodanes together with cembranoids.…”
Section: Resultsmentioning
confidence: 88%
“…Our studies of S. flexibilis have led to the isolation of three new cembranes, flexibilins A–C ( 1 – 3 ), along with a known metabolite, (−)-sandensolide ( 4 ), and flexibilin B ( 2 ) displayed a moderate inhibitory effect on the release of elastase by human neutrophils. In addition to marine organisms, cembrane-type diterpenoids are also found in higher plants and bryophytes [34,35,36,37,38,39,40,41,42,43]. However, the carboxylic acid moieties exhibited in cembranes 1 and 2 are rarely found [35,44].…”
Section: Discussionmentioning
confidence: 99%